KING OF GOWA XIV THROUGH ISLAMIZATION IN BONE DURING 17TH CENTURY - Rahmawati (Jurnal Cakrawala Ilmiah, 2022)
Kingdom of Gowa – built approximately in 14th century, as well as officially to be an Islamic Kingdom on November, 09 1607 – Islamized many kingdoms in Sulawesi, Kalimantan, and Nusa Tenggara Islands. It had great military, especially in Sultan Hasanuddin era. This empire was able some times to conquer VOC offense. Unfortunately, Gowa fell by divide et impere, a strategy of VOC collaborated with Arung Palakka, king of Bone. Eventually, Sultan Hasanuddin signed a letter of agreement called Bongayya agreement. It said Sultan Hasanuddin must give Gowa up to VOC. Then, since signing the agreement in Batavia on 18th November 1667, the empire of Gowa officially fell to VOC. Indeed, that was the last of triumph of the greatest and strongest kingdom ever in Sulawesi called Gowa.